A new species of Leptolalax (Anura: Megophryidae) from Vietnam - Rowley, Jodi J. L.; Dau, Vinh Q.; Cao, Trung T. (Zootaxa, 2017)
We describe a new, medium-sized Leptolalax species from north central Vietnam. Leptolalax puhoatensis sp. nov. is distinguished from its congeners by a combination of having a body size range of 24.2–28.1 mm in eight adult males and 27.3–31.5 mm in three adult females; distinct dorsolateral markings including blackish spots on the flank and dark canthal and/or temporal streaks; males with a reddish-brown venter, often with faint white dusting and females with a pale pink venter; skin on dorsum with tiny, indistinct, low tubercles in preservative, more distinct and forming low dorsal ridges on dorsal surface in life; toes with webbing basal and narrow lateral fringes; iris copper in upper half and golden in lower half; and a call consisting of a single note and a dominant frequency of 4.9–5.6 kHz (at 22.3–25.8º C). Uncorrected sequence divergences between L. puhoatensis sp. nov. and all homologous 16S rRNA sequences available for known species in the genus are ≥6.3%.